In vitro study of antimicrobial activity of Acalypha indica Linn. extract - Ishak, Farah Dayana; Mat So'ad, Siti Zaiton; Asmali Jauhari, Anis Hazirah; Mashud, Nini Nadira; Mohd Hassan, Norazian (Bentham Open, 2013)
The objective for this research undertaken was to evaluate Acalypha indica extracts for their antimicrobial potential. Fresh plant samples were extracted via maceration in increasing polarity using petroleum ether, chloroform and methanol. Antimicrobial activity of the extracts was assessed using disc diffusion assay and minimum inhibitory concentration. It was observed that the crude methanol leaves, stembark and chloroform stembark extracts exhibit antimicrobial activity towards both Staphylococcus aureus bacteria and Candida albicans fungi. The inhibition zones recorded in milimeters by the chloroform stembark extracts were 9.57±0.51 (200 mg/mL), 8.33±0.58 (100 mg/mL) and 7.33±0.58 (50 mg/mL) while methanol stembark extract recorded inhibition zones at 13.67±0.58 (200 mg/mL), 10.00±1.00 (100 mg/mL) and 9.33±0.58 (50 mg/mL) against S. aureus. Antifungal activity was also detected against C. albicans as the chloroform stembark extract produced inhibition zones of 14.33±0.58 (200 mg/mL), 13.33±0.58 (100 mg/mL) and 12.67±0.58 (50 mg/mL) while the methanol stembark extract resulted in inhibition zones of 15.33±0.58 (200 mg/mL), 14.33±0.58 (100 mg/mL) and 13.0±0.00 (50 mg/mL). In the case of crude methanol leaves extract, the extract produced inhibition zones of 19±0.58 (200 mg/mL), 13±1.00 (100 mg/mL) and 10±1.00 (50 mg/mL) against S. aureus while against C. albicans, the extract recorded inhibition zones of 15±0.58 (200 mg/mL), 14±0.00 (100 mg/mL) and 13±0.00 (50 mg/mL). The chloroform stembark crude extract developed a medium MIC value of 0.938 mg/mL while both methanol crude extracts produced a strong MIC value of 0.469 mg/mL during the minimum inhibition concentration screening against Candida albicans.